The Evolution of NIMHANS Neurotrauma Care - Bhat, Dhananjaya I.; Devi, B. Indira; Shukla, Dhaval; Kulkarni, Akshay V. (Indian Journal of Neurotrauma, 2020)
Neurotrauma services in NIMHANS, Bangalore, have been evolving since its inception in 1958. At present, it is a major referral center for Karnataka and surrounding districts of the southern states. It has many firsts to its credit, from having a separate building to having dedicated trauma teams to manage the service 24/7. It has made rapid strides in healthcare delivery based on data-driven evidence, improvisation with Lean sigma approach, and contribution through research and publications. This center has won best Neurotrauma center award in 2010.
Keywords: NIMHANS; history of neurotrauma NIMHANS; lean sigma; neurotrauma management in India; neurotrauma tam